Size and Morphology of Sella Turcica in Malay populations: A 3D CT Study - Hasan, Haider Ali; Alam, Mohammad Khursheed; Yusof, Asilah; Mizushima, Hidemoto; Kida, Akio; Osuga, Naoto (The Society for Hard Tissue Regenerative Biology, 2016)
The purpose of this study was to analyse the linear and area dimensions and morphological shape of sella turcica to determine if differences exist due to gender or age and compared with available global data. A total of 183 (113 men and 70 women) Malay subjects who had their computed tomography (CT) scan at the Radiology Department, Hospital University Sains Malaysia (HUSM) for ordinary diagnosis not related to craniofacial deformities. The selected age groups were divided into four groups as children (0-6 years), preadolescents (7-12 years), adolescents (13-20 years) and adults (21-35 years). The images were processed using Mimics V17.0 software. Conventional measurements included three different heights of the sella turcica (anterior, posterior, median), its length, diameter, area and width, measured in relation to the Frankfort reference line (FH). Morphometric methods were used to assess shape. No significant differences in size of the sella were found except at sella height anterior between genders. When age was evaluated, significant differences were found among all age groups. The study found that sella turcica presented with a three different shapes: in a U shape (57.9 %), in a J shape (24.5 %) and shallow (17.5 %). Sella shape and dimensions reported in the current study can be used for discovering Pathological enlargement of the pituitary fossa and may also be helpful in providing reference data in the assessment of racial, gender and age specific variation in Malay population